(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
Artificial intelligence (AI) is the means of revolutionizing the field of education. More specifically, the process of curriculum transactions is being influenced by the new generation technology of AI. It is providing vast options of interaction between teacher and taught. The other stakeholders of education system are also getting benefitted by the application of AI. However, it deserves mention that some unethical practices by which the stakeholders including learners can get harm with the applications of AI. Therefore, framing and implementation of relevant laws, and continuous supervision to ensure ethical use of AI in education is the need of the hour. This article describes some of the key ethical issues related to the use of AI in curriculum transaction. In addition, some ideal ethical practices have been recommended to ensure skilful applications of AI to provide standard educational services.